Plant Uptake of Arsenic, Cadmium, and Lead by Hemp, Mustard, and Kale Grown in Coconut Coir Substrate - Harrison A. Meekins; Paul R. Fisher; Jonathan D. Judy; Kevin M. Folta (HortScience)
Medicinal and food crops including hemp (Cannabis sativa L.) are routinely tested for heavy metal (HM) contaminants including As, Cd, and Pb per regulatory guidelines. Heavy metals have been found in greenhouse substrates, including peat and coconut coir, and are commonly used in hemp production, which underscores the need to evaluate the risk of HM contamination of hemp from these production inputs. The objective was to quantify uptake of As, Cd, and Pb in coconut coir substrate into shoot tissue using bioassays and compare heavy metal uptake between brassicas and hemp. In Expt. 1, ‘Maverick’ hemp was grown for 8 weeks in a greenhouse in coconut coir–filled containers that were dosed before planting with 0.0, 0.5, 1.0, 4.8, or 9.7 mg of soluble Cd and Pb per kg of dried coir (mg·kg−1). ‘Maverick’ hemp, ‘Savanna’ mustard (Brassica juncea L.), and ‘Red Russian’ kale (Brassica oleracea L.) seedlings were also grown in a growth chamber for 4 weeks in propagation trays with HM application levels of 0, 3, 15, 30, and 60 mg·kg−1 of Cd and Pb (Expt. 2) or 0.0, 0.5, 1.0, 3.0, and 5.0 mg·kg−1 of As, Cd, and Pb (Expt. 3). In all experiments, Cd tissue concentration and mg of Cd per plant increased as HM levels in the substrate increased. Cd exhibited the greatest plant uptake, followed by As and then Pb. Average As and Cd concentrations in hemp tissue were above a typical regulatory threshold for medicinal cannabis of 0.2 mg·kg−1 of dried tissue in all experiments when HM was applied at 0.5 mg·kg−1 of substrate or greater. In contrast, Pb was the least plant-available HM, with shoot tissue concentrations in hemp below the regulatory threshold of 0.5 mg·kg−1 except when substrate Pb reached 30 or 60 mg·kg−1. The results therefore indicate a higher potential risk of contamination from As and Cd for medicinal hemp than Pb at a given HM concentration. Mustard had the greatest accumulation of As and Cd, followed by kale and hemp, emphasizing that HM accumulation is also of concern for controlled environment production of brassica crops.